Leadership beyond narcissism: On the role of compassionate love as individual antecedent of servant leadership - Tim Brouns; Kai Externbrink; Pablo Salvador Blesa Aledo (Administrative Sciences, 2020)
While we already know a lot about the outcomes and boundary conditions of servant leadership, there is still a need for research on its antecedents. Building on the theory of purposeful work behavior and further theorizing by van Dierendonck and Patterson (2015), we examine if leaders' propensity for compassionate love will evoke servant leadership behavior. At the same time, we contrast compassionate love to leaders' narcissism as psychological counterpart to compassionate love, because narcissism is not associated with leader effectiveness, but with leader emergence instead. We collected data from 170 leader-follower-dyads in a field study in Germany, while measuring leaders' compassionate love and narcissism, and followers' perceptions of servant leadership. We found a positive association between leaders' compassionate love and servant leadership behavior, while narcissism was negatively associated with servant leadership. Theoretical and practical implications, as well as pathways for future research are discussed.
Keywords: 350; servant leadership; compassionate love; narcissism; antecedents